BLOCKCHAIN AND ITS APPLICATION TO PUBLIC SECTOR ACCOUNTING IN INDONESIA - Irawan, Irawan; Ku Arifin, Ku Halim (Proceeding International Seminar of Islamic Studies, 2024)
The main purpose of this research is to analyze the existing literature on the importance of Blockchain and its possible impact on the Public Sector Accounting In Indonesia. This research design applies literature study approach on blockchain and its application to Public Sector Accounting in Indonesia. The data analysis technique is done by clarifying some of the terminological confusion that exists with regards to blockchain, and what challenges could be the future of this technology. The results of this study find that Blockchain as a public sector accounting application in Indonesia involves an important transformation of the traditional accounting system, with modification consequences that result in high levels of performance. One of the main contributions of this research is the importance of understanding information technology, being one of the first to analyze the impact of Blockchain in public sector accounting in Indonesia. Data and information used in the preparation of blockchain planning documents must be data that has been inputted into the Regional Development Information System (RDIS/SIPD).